2017
DOI: 10.1002/ejsp.2266
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the validity of co‐occurrence on automatic and deliberate evaluations

Abstract: Co‐occurrence of an object and affective stimuli does not always mean that the object and the stimuli are the same valence (e.g., false accusations that Richard is a crook). Contemporary theory posits that information about the (in)validity of co‐occurrence has stronger influence on deliberate than automatic evaluation. However, available evidence supports that hypothesis only when the (in)validity information is delayed. Further, the existing evidence is open to alternative methodological accounts. In six hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Even after people have rehearsed and expressed their initial impression, once they confront new evidence that is believable, they can correct it, even at the implicit level. This extends earlier work that suggested that information can be negated only if we know that it is false at the time we learn it (7) or very soon after if there is extensive rehearsal of the information (8) but that such negations are less impactful if we only later discover that the information is false. This earlier work suggested (7) that once an association has formed through the associative processes that are argued to underlie implicit cognition, it cannot be easily corrected thereafter.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Even after people have rehearsed and expressed their initial impression, once they confront new evidence that is believable, they can correct it, even at the implicit level. This extends earlier work that suggested that information can be negated only if we know that it is false at the time we learn it (7) or very soon after if there is extensive rehearsal of the information (8) but that such negations are less impactful if we only later discover that the information is false. This earlier work suggested (7) that once an association has formed through the associative processes that are argued to underlie implicit cognition, it cannot be easily corrected thereafter.…”
Section: Discussionsupporting
confidence: 84%
“…ref. 8). Thus, in Study 5, we tested how the delayed discovery of the reliability of information influenced implicit impression correction.…”
Section: Studies 3 To 6: Rumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent research suggests that contrary to conventional wisdom, procedural learning may take place with conscious awareness of implicit skills (Tran and Pashler 2017). Contrary to a widespread assumption of contemporary evaluation theory, automatic evaluations are probably not any less sensitive to validity information than deliberate evaluation are (Moran et al 2017). Researchers have demonstrated that people can accurately predict and consciously report their own implicit attitudes (Hahn et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…For each actor, participants also responded to three questions in the format of How likable [trustworthy, friendly] is Eddie Murphy? Using response options that ranged from 1 (Extremely unlikeable [untrustworthy; unfriendly]) to 9 (Extremely likeable [trustworthy; friendly]) (adapted from Moran, Bar-Anan,& Nosek, 2017). The order of the six questions (three for each actor) was randomized for each participant.…”
mentioning
confidence: 99%